The Optimum Yield of Nannochloropsis sp Microalgae from the Lipid Cultivation and Extraction Process with Soxhlet Method - Lukmanul Hakim; Rusdianasari Rusdianasari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The purpose of this study was to determine the optimal growth of Nannochloropsis sp microalgae cell density observations in the cultivation process and to see the percent yield of lipids from microalgae Nannochloropsis sp. through the extraction process with the Soxhlet method using n-hexane and ethanol solvents at a ratio of 1:1, 1:2, 1:3, 1:4 and 1:5. The optimal amount of cell density during the cultivation process has obtained an average of 32,206 x 104 cells/ml on day of 9th, and the optimal lipid yield was in the ratio of hexane: ethanol 1:1 with a value of 32.13%. These results show that the optimal conditions for yield can be obtained and also has the potential as a raw material biodiesel production.